Cassidulina teretis Tappan and Cassidulina neoteretis new species (Foraminifera): stratigraphic markers for deep sea and outer shelf areas - Seidenkrantz, Marit-Solveig (Journal of Micropalaeontology, 1995)
Fossil versus Recent specimens allocated to Cassidulina teretis Tappan display slight differences in both ecological distribution and morphology. This has led to a re-examination of specimens from the North Atlantic region. The study was mainly based on scanning electron microscopy. It resulted in the division of the plexus into two species with different stratigraphical and partly different environmental distributions: Cassidulina teretis Tappan and Cassidulina neoteretis n. sp. A distinction between C. teretis and C. neoteretis provides a new biostratigraphical marker and may also prove useful in ecological studies. C. teretis had its first occurrence during the Middle to Upper Miocene and its last well-documented occurrence shortly after the palaeomagnetic Brunhes/Matuyama boundary in the Norwegian Sea, whilst it apparently disappeared from the North Atlantic as early as a little after the Gauss/Matuyama boundary. C. neoteretis presumably evolved from C. teretis between about 2.0 and 2.3 Ma in the northern North Atlantic and migrated northward inhabiting the Norwegian Sea as C teretis became extinct here at about 0.7 Ma. All Recent specimens belong to C. neoteretis. Specimens of C. teretis have been documented from both arctic and boreal regions in inner shelf to bathyal environments (between about 50 and 2000 m water depth), whereas the Recent distribution of C. neoteretis is slightly more limited: arctic and cold boreal regions at water depths between 150 and 3000 m, most commonly between 1000 and 1500 m.